Amphinema modernisme, a new Pandeid (Cnidaria: Anthomedusae) from the Southern Ocean - Bouillon, Jean; Gili, Josep Maria; Pagès, Francesc; Isla, Enrique (Polar Biology, 2000)
4 pages, 1 figure, 1 table A new species of pandeid anthomedusa, Amphinema modernisme, is described from a single and complete specimen collected by a mid-water sediment trap placed at 500 m depth in open waters, over a 1066-m bottom in the Drake Passage near the South Shetland Islands. This new Amphinema is characterized by an egg-shaped apical chamber, partitioned by four narrow sacciform centrifugal prolongations of the radial canals, perradial gonads and cellular strands linking the radial canals to the exumbrella. Its morphological features are compared with those of the eight other species of the genus Amphinema and a new diagnosis for this genus is presented